Social and structural determinants of HIV treatment and care among black women living with HIV infection: a systematic review: 2005–2016. Issue 4 (3rd April 2018) - Geter, Angelica; Sutton, Madeline Y.; Hubbard McCree, Donna
ABSTRACT: Black/African American (black) women comprised 59% of women living with HIV at the end of 2014 and 61% of HIV diagnoses among women in 2015. Black women living with HIV infection (BWLH) have poorer health outcomes compared with women of other races/ethnicities; social and structural determinants are often cited as barriers and facilitators of care. The objective of this qualitative review was to identify social and structural barriers and facilitators of HIV treatment and care among BWLH. The systematic review was conducted in six-stages using databases such as PubMed, PsycINFO, and Google Scholar: 1) searched for studies that enrolled BWLH published between January 2005 and December 2016, 2) excluded unpublished reports and commentaries, 3) limited the search to our primary keywords, 4) limited our search to studies that included participants living with HIV infection that were >60% black and 100% female, 5) extracted and summarized the data, and 6) conducted a contextual review to identify common themes. Of 534 studies retrieved, 16 were included in the final review. Studies focused on: ART medication adherence ( n = 5), engagement/retention in care ( n = 4), HIV care and treatment services ( n = 3), viral suppression ( n = 1), and addressing multiple HIV care outcomes ( n = 3). Main barrier themes included lack of family and/or social support, poor quality HIV services, and HIV-related stigma, particularly from healthcare providers; facilitator themes included resilience, positive relationships between case management and support services, high racial consciousness, and addressing mental health. Interventions that decrease these noted barriers and strengthen facilitators may help improve care outcomes for BWLH. Also, more HIV stigma-reduction training for healthcare providers may be warranted.